2022
DOI: 10.4236/jep.2022.131008
|View full text |Cite
|
Sign up to set email alerts
|

Different Detection and Treatment Methods for <i>Entamoeba histolytica</i> and <i>Entamoeba dispar</i> in Water/Wastewater: A Review

Abstract: Entamoeba histolytica is an anaerobic parasitic protozoan and well known as a human pathogen, while its close relative, Entamoeba dispar, also possesses similar characteristics as an infectious agent. These microorganisms are generally transmitted in fecal-contaminated water. However, E. dispar present in industrial wastewater is also capable of creating biofilms that can cause adverse impacts in piping networks. Therefore, it is important to detect both of these protozoan species in water and to find a cost-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…dispar was reported to be a pioneering agent in the formation of biofilms, as observed in an industrial wastewater deep injection disposal well in Florida where it was the most abundant microorganism. This aspect is probably implied in the occurrence and persistence of this microorganism in water [163].…”
Section: Drinking Water Involvement In Entamoeba Spp Infectionsmentioning
confidence: 88%
“…dispar was reported to be a pioneering agent in the formation of biofilms, as observed in an industrial wastewater deep injection disposal well in Florida where it was the most abundant microorganism. This aspect is probably implied in the occurrence and persistence of this microorganism in water [163].…”
Section: Drinking Water Involvement In Entamoeba Spp Infectionsmentioning
confidence: 88%
“…Therefore, a simplification and evolution of such methods towards the identification of the parasite is desirable. It must be noted that standardized methods of elution and concentration from water had not yet been developed for some protozoans, such as Entamoeba species [210]. A recent study demonstrated that dead-end ultrafiltration (DEUF) coupled with quantitative PCR allowed consistent detection of C. cayetanensis DNA in surface water samples [237].…”
Section: Methods For the Detection/identification Of Protozoans In Fo...mentioning
confidence: 99%